Factors Associated With Unilateral Hearing Loss and Impact on Communication in US Adults. (23rd March 2021) - Choi, Janet S.; Wu, Franklin; Park, Soyun; Friedman, Rick A.; Kari, Elina; Volker, Courtney C. J.
Abstract : Objective: To investigate the factors associated with unilateral hearing loss (UHL) and its impact on communication in US adults. Study Design: Cross‐sectional study. Setting: Nationally representative sample of US adults. Methods: We analyzed data from the 2011‐2012 and 2015‐2016 National Health and Nutritional Examination Survey, in which participants aged 20 to 69 years completed an audiometric evaluation (n = 8138). UHL was defined as a speech frequency pure‐tone average ≥25 dB in the worse hearing ear and <25 dB in the better hearing ear. Logistic regression was used to examine the association between UHL and relevant factors. Results: The prevalence of UHL was 8.1% (95% CI, 7.3%‐9.0%) in US adults. Factors associated with UHL included older age, male sex, white race, lower level of education, diabetes, cardiovascular disease, and off‐work noise exposure. Among adults with UHL, 40% (95% CI, 32%‐48%) reported subjective trouble with hearing, a rate higher than the 12% (95% CI, 11%‐14%) among normal‐hearing adults. After adjusting for relevant factors, adults with UHL were more likely to report difficulties with following conversations with noise (odds ratio [OR], 1.7; 95% CI, 1.2‐2.5) and frustration when talking to family and friends (OR, 3.0; 95% CI, 1.9‐4.6). Higher levels of communication difficulties were observed with worsening level of UHL. Conclusions: Adults with UHL report significant communication difficulties in comparison to normal‐hearing adults. Further research is needed to understand the psychosocial impact of UHL on adults and ways to improve communication support for adults with UHL.